HUBUNGAN MENYIRIH DENGAN KEADAAN JARINGAN PERIODONTAL PADA ORANG YANG MENYIRIH DI BANJAR SEDANA MERTHA KOTA DENPASAR TAHUN 2012 - Ni Wayan Arini (Jurnal Kesehatan Gigi (Dental Health Journal), 2013)
Dental health or oral health is often refered as the welfare Of the mouth, including the teeth and sipporting structures and free tissue from disease and pain, and mouth as well as supporting the tissue to function optimally. In Indonesia, periodontal desease is  the second most illness  suffered by the community (±73.50%),and amounted to 4-5% of the population suffer from advanced periodontal desease or guingival in the presence of lessions on the oral mucosa. The research good is to find a relationship of chewing with conditions of periodontal tissues were chewing of banjar Sedana  Mertha of Denpasar in 2012.The method of the study is descriftive research with cross sectional approach. The population of this research was 20 people. Results of the research concluded on the 20 respondents who had a habit of chewing on get as many as 14 women and 6 man.The higest score is the state of the periodontal tissues by 14 respondent shallow pockets, pockests in  5 respondents, tartar 1 respondent. Result of statistic Test of Pearson obtained r=0,669 and p=0.001. This research showing a significant correlation between habit with a condition of periodontal tissue